2017
DOI: 10.1038/ijo.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Does activation of midbrain dopamine neurons promote or reduce feeding?

Abstract: Chemogenetic activation of VTA DA neurons or VTA to NAc pathway disrupts feeding patterns. Increased activity of mesolimbic DA neurons appears to both promote and reduce food intake, by facilitating both the initiation and cessation of feeding behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 51 publications
7
40
1
Order By: Relevance
“…These counts produced an average selectivity of mCherry-expression for TH positive cells of 95.8% and a transfection efficiency of 24.8% ( Fig. 4c), which are comparable to similar measures of selectivity in TH::Cre rats 20,[31][32][33][34][35] . We also observed mCherry expressing TH positive processes in the NAc (Fig.…”
Section: Chemogenetic Targeting Of Vta Dopamine Neurons In Th::cre Rasupporting
confidence: 66%
“…These counts produced an average selectivity of mCherry-expression for TH positive cells of 95.8% and a transfection efficiency of 24.8% ( Fig. 4c), which are comparable to similar measures of selectivity in TH::Cre rats 20,[31][32][33][34][35] . We also observed mCherry expressing TH positive processes in the NAc (Fig.…”
Section: Chemogenetic Targeting Of Vta Dopamine Neurons In Th::cre Rasupporting
confidence: 66%
“…Both AA and Wistar rats very willingly consumed a large number of sucrose pellets even under ad libitum feeding of regular chow. Despite this, the D-amphetamine caused significant reduction in sucrose consumption in the satiety test, which was exactly what was predicted based on our previous study (Oinio et al 2017) and by the literature, because Damphetamine is a drug known to induce anorexic effects (Wise 2006;Melrose et al 2016;Boekhoudt et al 2017). It can be clearly seen in both strains that D-amphetamine reduced sucrose intake dose dependently, and the highest dose almost abolishes sucrose eating totally.…”
Section: Discussionsupporting
confidence: 87%
“…They found that general stimulation of hM3Dq in VTA reduced meal size, while at the same time increasing locomotor activity. Specific mesolimbic pathway DA activation disrupted feeding patterns by reducing mean meal size and duration but increased the frequency of meal initiations (Boekhoudt et al, 2017a). Although, the mesolimbic DA pathway seemed to both promote and reduce food intake in that study by facilitating feeding initiation and cessation behaviors (Boekhoudt et al, 2017a), chemogenetic stimulation in the same mesolimbic pathway in another study prevented anorexic weight loss in an activity-based rat model of anorexia (Foldi et al, 2017).…”
Section: Modulating Dopamine Signaling and Behavior With Chemogeneticsmentioning
confidence: 91%
“…It is widely believed that the DA mesolimbic pathway facilitates associative learning between food-related rewards and feedingrelated environments, with food or food-related cues initiating phasic mesolimbic DAergic firing and behaviors associated with acquiring food (Baik, 2013). Boekhoudt et al (2017a) investigated whether chemogenetic activation of midbrain DAergic neurons promoted or reduced feeding to establish a causal relationship between DAergic activity and food intake. They measured home-cage feeding patterns while concurrently stimulating hM3Dq in the SN pars compacta or selective VTA subpopulation projections toward the NAc, amygdala, or PFC.…”
Section: Modulating Dopamine Signaling and Behavior With Chemogeneticsmentioning
confidence: 99%
See 1 more Smart Citation